Temporomandibular disorders and their interaction with the body posture - José Miguel Montero Parrilla; Oleksandra Semykina; Leonora da Conceição Morais Chipombela (Editorial Ciencias Médicas, 2014)
Introduction: In recent years it has been suggested that temporomandibular disorders may be influenced by body posture. Objective: The objective of this paper is to characterize temporomandibular disorders based on their interaction with the postural variables. Methods: A descriptive cross-sectional observational study was conducted from February 2011 to March 2012, in which 122 students from 3rd. year at the Faculty of Dentistry underwent clinical examination in two stages. First, dental occlusion was examined and then postural examination was performed. Test of Krogh-Paulsen was applied for diagnosing temporomandibular disorders. Results: Regardless of postural type, the major signs and symptoms found were such as irregularities in mandible movements and joint clicking representing 45.1 % and 31.2 % respectively. 40.2 % of students had a Type B posture, followed by type D posture in 29.5 % of cases. Only 36 students were healthy. Right pelvis imbalance was the most common, and it was present in 48.4 % of the sample. Conclusions: For all possible test-Krogh Paulsen classifications of patients, imbalance of the right pelvis predominated. Patients with temporomandibular joint (TMJ) clicking had unbalanced pelvis and shoulders in the same direction but opposite to where the sign appeared. A strong relationship between postural changes and temporomandibular disorders was not evident.